Composition and Abundance Of Crustacea and Polychaeta In Mangrove Stands At Bulalo Kwandang District North Gorontalo Regency. - Abubakar Sidik Katili; Ramli Utina (Jambura Edu Biosfer Journal, 2019)
The aim of the study to determine the composition and abundance of Crustacea and Polychaeta based Mangrove stands in the village of Bulalo Kwandang District of North Gorontalo regency. The research conducted over four months. The method used is survey method and techniques of data collection was done by using a sample square. The data were analyzed by descriptive quantitative. The results showed that crustacea species which consists of 3 family, that is Portunidae, Sesarmidae, Ocypodidae, while the Polychaeta only one family that is Capitellidae family. At station 1 species which have the highest index of abundance that is Sesarma sp. Indv/m2 and 0.189 for species that have the lowest abundance index of 0.023 Indv/m2 Scylla serata. While at the station two species that have the highest abundance index Sesarma sp. of 0.188 Indv/m2 which has an index of abundance and low of Scylla serata the abundance index of 0.020 Indv/m2. The most abundance species found in the Rhizophora sp stands. Where species of the least discovered that the stand Avicenia sp.